Video laparoscopic intervention for an interstitial pregnancy after failure of clinical treatment - Szylit, Nilson Abrão; Podgaec, Sérgio; Traina, Evelyn; Oliveira, Rita de Cassia Sanches (São Paulo Medical Journal, 2012)
CONTEXT: Interstitial pregnancy is a rare form of ectopic pregnancy for which the best therapeutic course of action has yet to be determined. Surgical intervention entails a high risk of hemorrhage due to the great vascularization of the cornual region of the uterus. Case descriptions facilitate the analysis of results and aid clinicians in determining the most appropriate course of action in these situations. CASE REPORT: In a patient with an ultrasound diagnosis of interstitial pregnancy, clinical treatment using methotrexate was chosen. However, after one week, there was a marked decline in the serum level of the β subunit of chorionic gonadotropin hormone, although an ultrasound examination revealed embryonic cardiac activity. A second dose of the chemotherapy was administered. Embryonic cardiac activity persisted 48 hours later. Video laparoscopy was performed to achieve right-side cornual resection, which resulted in satisfactory resolution of the case.